Understanding Marawi’s Media Landscape for Peace and Sustainable Development - Latip-Yusoph, Sorhaila (MultiTech Publisher, 2024)
This study examines Marawi City's media landscape before, during, and after the 2017 siege, investigating existing outlets, media practitioner dynamics/safety challenges, and media's role in peacebuilding and sustainable development. Findings reveal a pre-siege thriving local press transitioning to intense national/international coverage during the siege, with local voices emerging through initiatives like